Code of Ethics and Position of Notary in Indonesia - Ong Argo Victoria; Ade Riusma Ariyana; Devina Arifani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The notary is authorized to make authentic deeds regarding all actions, agreements and provisions required by the laws and regulations and/or that the interested party wants to be stated in the authentic deed, guarantees the certainty of the deed creation date, keeps the deed, provides grosse, copies and excerpts of the deed , all of them as long as the deeds are drawn up, they are not assigned or exempted from other officials or other people as stipulated by law. Therefore, the general power (openbaar gezaag) based on the law assigns the officer concerned to produce written evidence as desired by the parties with authentic power. The approach method used in this study is primarily a descriptive analysis approach. In practical terms, By writing this research, it is hoped that it can provide valuable input for all parties involved in the implementation of the notary office and can also add insight to the notary regarding the problem of violating the code of ethics which results in criminal action. What is stated in the notary code of ethics made by the INI organization which is the only notary organization that is legally incorporated in accordance with UUJN. This means that all notaries must comply with the Notary Code of Ethics. What is stated in the notary code of ethics made by the INI organization which is the only notary organization that is legally incorporated in accordance with UUJN. This means that all notaries must comply with the Notary Code of Ethics. What is stated in the notary code of ethics made by the INI organization which is the only notary organization that is legally incorporated in accordance with UUJN. This means that all notaries must comply with the Notary Code of Ethics.